2008
DOI: 10.1007/s10661-008-0249-y
|View full text |Cite
|
Sign up to set email alerts
|

To address accuracy and precision using methods from analytical chemistry and computational physics

Abstract: In this work the pesticides were determined by liquid chromatography-mass spectrometry (LC-MS). In present study the occurrence of imidacloprid in 343 samples of oranges, tangerines, date plum, and watermelons from Valencian Community (Spain) has been investigated. The nine additional pesticides were chosen as they have been recommended for orchard treatment together with imidacloprid. The Mulliken population analysis has been applied to present the charge distribution in imidacloprid. Partitioned energy terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Kozmutza and Pico ´(2009), using DFT theory, the B3LYP exchange-correlation potential and the 3-21G* basis set, found that according to MPA, only one nitrogen atom (N14) possesses a positive charge. 57 This contrasts with the statement of Tomizawa and Casida (2000), who found a slightly positive charge on N8 (0.0315) using the MNDO-PM3 semi-empirical molecular technique. 63 In the same work, Tomizawa and Casida (2000) found that the insecticide desnitroimidacloprid presents a slight negative charge on N8 (À0.0063), indicating that the nitro group is (2008).…”
Section: Population Analysismentioning
confidence: 69%
See 1 more Smart Citation
“…Kozmutza and Pico ´(2009), using DFT theory, the B3LYP exchange-correlation potential and the 3-21G* basis set, found that according to MPA, only one nitrogen atom (N14) possesses a positive charge. 57 This contrasts with the statement of Tomizawa and Casida (2000), who found a slightly positive charge on N8 (0.0315) using the MNDO-PM3 semi-empirical molecular technique. 63 In the same work, Tomizawa and Casida (2000) found that the insecticide desnitroimidacloprid presents a slight negative charge on N8 (À0.0063), indicating that the nitro group is (2008).…”
Section: Population Analysismentioning
confidence: 69%
“…Numerous procedures have been used for this purpose, such as Mu ¨liken Population Analysis (MPA), 54 Hirshfeld Population Analysis (HPA), 55 and Natural Population Analysis (NPA). 56 Although MPA is the most widely used approach, 57 Weinhold, Reed and Weinstock (1985) stated that MPA is insufficient in many cases; thus, the authors developed natural population analysis (NPA), based on natural atomic orbitals (NAOs), as a complete orthonormal set for optimally describing effective atom-like constituents within a molecular environment. 56,58 Other researchers relate that HPA is more accurate, as it can predict reactive sites within a molecule better than MPA, NPA and fitted electrostatic potentials.…”
Section: Population Analysismentioning
confidence: 99%